Female rats learn trace memories better than male rats and consequently retain a greater proportion of new neurons in their hippocampi. - Dalla, Christina; Papachristos, Efstathios B; Whetstone, Abigail S; Shors, Tracey J (Proc Natl Acad Sci U S A, 2009)
Learning increases the survival of new cells that are generated in the hippocampal formation before the training experience, especially if the animal learns to associate stimuli across time [Gould E, Beylin A, Tanapat P, Reeves A, Shors TJ (1999) Nat Neurosci 2:260-265]. All relevant studies have been conducted on male rats, despite evidence for sex differences in this type of learning. In the present study, we asked whether sex differences in learning influence the survival of neurons generated in the adult hippocampus. Male and female adult rats were injected with one dose of bromodeoxyuridine (BrdU; 200 mg/kg), to label one population of dividing cells. One week later, half of the animals were trained with a temporal learning task of trace eyeblink conditioning, while the other half were not trained. Animals were killed 1 day after training (12 days after the BrdU injection). Hippocampal tissue was stained for BrdU and a marker of immature neurons, doublecortin. Both sexes learned to emit the conditioned eyeblink response during the trace interval. As a consequence, more new neurons remained in their hippocampi than in sex-matched controls. In individual animals, the number of surviving cells correlated positively with asymptotic performance; those that expressed more learned responses retained more new neurons. However, animals that learned very well retained even more new cells if they required many trials to do so. Because females emitted more learned responses than males did, they retained nearly twice as many new cells per unit volume of tissue. This effect was most evident in the ventral region of the hippocampal formation. Thus, sex differences in learning alter the anatomical structure of the hippocampus. As a result, male and female brains continue to differentiate in adulthood.
Keywords: Animals; Bromodeoxyuridine; Cell Survival; Conditioning, Eyelid; Estrogens; Female; Hippocampus; Immunohistochemistry; Learning; Male; Memory; Neurogenesis; Neurons; Rats; Rats, Sprague-Dawley; Sex Factors